Effect of an essential oilcontaining antimicrobial mouthrinse on specific plaque bacteria in vivo - Daniel H. Fine (Blackwell Synergy, 2007)
Aim: This study was conducted to investigate the effect of rinsing with an essential oil-containing mouthrinse on levels of specific supra and subgingival bacteria in subjects with gingivitis. Material and Methods: Fifteen subjects meeting entry criteria completed this randomized, controlled, double-blind, crossover study. Subjects were required to have X1000 target organisms per millilitre in pooled samples from two subgingival sites. Following sampling of supra and subgingival plaque, subjects began twice-daily rinsing for 14 days with either an essential oil-containing mouthrinse (Cool Mint Listerines Antiseptic) or a negative control. Supra and subgingival plaque was again sampled on day 15, and the procedure repeated after a 1-week washout period with subjects using the alternate rinse. Results: Compared with the negative control, the essential oil mouthrinse produced significant reductions in supragingival plaque levels of Veillonella sp., Capnocytophaga sp., Fusobacterium nucleatum, and total anaerobes ranging from 52.3 to 88.5% (po0.001 except for Veillonella, p50.002); respective reductions in subgingival plaque ranged from 54.1 to 69.1% (po0.001). Conclusions: Rinsing with the essential oil mouthrinse can have an impact on the subgingival plaque flora. This study provides additional evidence indicating that reduction in supragingival plaque can reduce levels of subgingival plaque.